Backlands : a novel of the American West - McGarrity, Michael (Dutton, 2014)
Catapulted into early adulthood after the death of an older brother he idolized, eight-year-old Matthew Kerney assumes difficult responsibilities to save the family ranch against a backdrop of the Great Depression and a drought-stricken Tularosa Basin.